The influence of the pharmacodynamic properties of drugs on indications for their use: Sodium-glucose cotransporter 2 inhibitors (SGLT2 inhibitors) - Denda Nikola I.; Maletin Nemanja Z.; Atanasković Marko B.; Vučković Biljana A.; Rašković Aleksandar L. (Hospital Pharmacology)
Introduction: Sodium-glucose cotransporter type 2 (SGLT2) inhibitors play a crucial role in type 2 diabetes treatment, exerting effects on proximal tubules to reduce glucose reab-sorption and enhance urinary excretion, offering cardiovascular and renoprotective benefits. This study aims to explore the pharmacodynamic advantages of SGLT2 inhibitors, expanding their therapeutic indications and assessing variations in pharmacological effects among different representatives. Methods: A thorough review of literature from 2000 to 2023 via PubMed focused on SGLT2 inhibitors' pharmacology and clinical impact on T2DM, heart failure, and chronic kidney disease. Twenty relevant studies were analyzed to understand differences between these inhibitors, refining their efficacy and safety profiles. Topic: On May 20, 2024, 16 original human studies examining the effects of SGLT2 inhibitors were found. Additionally, 4 original animal studies investigating the impact of SGLT2 inhibitors on laboratory mice were discovered. Conclusion: SGLT2 inhibitors show promise in improving patients' quality of life and reducing diabetes-related complications. Continuous safety and efficiency monitoring is crucial for optimizing their therapeutic use, given limited data on their long-term safety and comparative effectiveness.